2013
DOI: 10.1007/s00216-013-7231-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of native and APTS-labeled N-glycans by capillary electrophoresis/time-of-flight mass spectrometry

Abstract: The glycosylation of proteins is of particular interest in biopharmaceutical applications. The detailed characterization of glycosylation based on the released carbohydrates is mandatory since the protein stability, folding, and efficacy are strongly dependent on the structural diversity inherent in the glycan moieties of a glycoprotein. For glycan pattern analysis, capillary electrophoresis with laser-induced fluorescence using 8-aminopyrene-1,3,6-trisulfonic acid (APTS)-labeled glycans is used frequently. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…An ammonium hydroxide buffer system was explored as the background electrolyte that can facilitate regeneration of the bare fused‐silica capillary surface during analysis. Initial efforts were spent on testing a previously reported alkaline BGE system . However, soon it was realized that the BGE of 0.7 M ammonia, 0.1 M ɛ‐aminocaprioic acid, 70% methanol as previously reported generated very high mass spectrometry background, preventing effective glycan identification.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An ammonium hydroxide buffer system was explored as the background electrolyte that can facilitate regeneration of the bare fused‐silica capillary surface during analysis. Initial efforts were spent on testing a previously reported alkaline BGE system . However, soon it was realized that the BGE of 0.7 M ammonia, 0.1 M ɛ‐aminocaprioic acid, 70% methanol as previously reported generated very high mass spectrometry background, preventing effective glycan identification.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the lack of a fluorophore for laser‐induced fluorescence (LIF) detection and charged groups for mass spectrometry (MS) identification, N‐linked glycan analysis is currently carried out by releasing the glycans from the proteins using PNGase‐F enzyme digestion, followed by labeling with a fluorescence dye. It has been previously reported that adding a fluorescence tag greatly facilitates both chromatographic and electrophoretic separation of the N‐linked glycans . Therefore, these fluorescence dyes are usually optimized not only for sufficient fluorescence quantum yield, but also for high separation efficiency and strong MS response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bunz et al described both alkaline and acidic BGE systems that could be used for the determination of APTS-labeled mAb glycans by CE-TOF-MS [119, 120]. The CE-MS methods were then compared against to two CGE-LIF methods commonly used for routine glycan analysis.…”
Section: Applicationsmentioning
confidence: 99%
“…For CE, 8-aminonaphthalene-1,3,6-trisulfonic acid (ANTS) (Guttman et al 1994) and 8-aminopyrene-1,3,6-trisulfonic acid (APTS) (Guttman et al 1996;O'Shea et al 1998) are often employed for labeling because they provide a unique charge to mass ratio for all uncharged oligosaccharides in addition to sensitive LIF detection. A drawback of these labels is their relatively low ionization yield in electrospray ionization mass spectrometry (ESI-MS) (Pabst et al 2009;Bunz et al 2013a).…”
Section: Introductionmentioning
confidence: 99%